052 APOE-ε4 is associated with impaired sleep-dependent memory consolidation in healthy carriers. (3rd May 2021) - Djonlagic, Ina; Guo, Mengshuang; Igue, Moroke; Kishore, Divya; Marshall, Lisa; Malhotra, Atul; Stickgold, Robert
Abstract: Introduction: The Apolipoprotein E (APOE)-ε4 genotype is a marker of susceptibility for late-onset Alzheimer's disease (AD). Sleep disturbances may accelerate the aging process and increase the risk for future development of cognitive impairment and dementia. Given that the pathophysiological process of AD can predate its clinical manifestations by years or even decades, the aim of this study was to assess the role of the APOε4 allele on sleep-dependent memory consolidation in cognitively healthy adults. Methods: 16 healthy APOE-ε4 carriers (mean age=49.9±13.7) and 32 healthy non-carriers (age=45.7±12.9) were included in the main analysis. Baseline screening included the Epworth Sleepiness Scale, Morningness-Eveningness scale, Wechsler Adult Intelligence Scale (WAIS) and Beck Depression Inventory (BDI), as well as a baseline polysomnogram (PSG), which also served as an adaptation night. Participants subsequently underwent an overnight testing session, which included computer sessions of the Psychomotor Vigilance Task (PVT) and the declarative Verbal Paired-Associates Task (VPA) in the evening followed by a full night PSG and repeat PVT and VPA sessions in the morning. For further reference, we added an age matched group of 16 non-carriers with newly diagnosed obstructive sleep apnea (OSA, age=48.1±15.1), who underwent the same study procedures. Results: APOE-ε4 carriers had higher BDI (p=0.04) and ESS (p=0.01) scores than non-carriers. There were no significant group differences for sleep macrostructure. Evening VPA performance was similar for both groups (p=0.77). The following morning, APOE-ε4 carriers improved by 7.5±6.4 % from the evening before, compared to 13.5±7.0% for the healthy non-carriers (p=0.005). OSA subjects improved by 5.0± 8.1%, which was similar to APOE-ε4 carriers (p=0.34). Conclusion: To our knowledge, this is the first study to reveal that healthy APOE-ε4 carriers while showing similar initial learning (encoding) on a declarative memory task compared to healthy controls, exhibit a deficit in sleep-dependent memory consolidation, similar to patients with obstructive sleep apnea. Consequently, this study provides evidence that impaired sleep-related memory processes could be an important harbinger in otherwise healthy individuals, who are at high risk for AD. Support (if any): NIH grant # K23HL103850 (Ina Djonlagic) and American Sleep Medicine Foundation grant #54-JF-10 (Ina Djonlagic)